HIGH EFFICIENCY, HETEROSIS, AND HOMEOSTASIS IN MITOCHONDRIA OF WHEAT - Sarkissian, Igor V. (1969)
Mitochondria of a wheat hybrid 31MS × 28 when assayed polarographically exceeded mitochondria of parents of the hybrid in ADP:O ratios and in respiratory control when they utilized alpha-ketoglutarate, malate, and succinate. The ADP:O ratios of the hybrid mitochondria for the three substrates were 5.8 ± 0.2, 3.8 ± 0.15, and 3.4 ± 0.2, respectively. High P:O ratios were also observed in manometric assays. Mixtures of parental mitochondria exceeded averages of the parents, i.e., they exhibited complementation and approached activities of hybrid mitochondria. Complementation was observed only with NAD-linked substrates. Dinitrophenol uncoupled all mitochondria, but uncoupling was smallest in hybrid mitochondria. Hybrid mitochondria had the greatest ATPase activity. Mixtures exhibited complementation in ATPase activity. ATPase activity was stimulated least in hybrid mitochondria and in parental mixtures. The results were discussed from the point of view that the high P:) ratios gave us direct evidence that heterosis is indeed characterized by high efficiency. It is also pointed out that because of consistent repeatability and their specificity to hybrids, P:O ratios studied in rapidly isolated mitochondria of hybrids may give us revealing information on supramaximal efficiency of oxidative phosphorylation.